1864 Terr. of Mont. Acts 355 - (:unkn) unknown (My University, 1865)
§ 1 [Deadly weapons]: Prohibited the concealed carry of any pistol, Bowie-knife, dagger, or other deadly weapon. Violators fined not less than twenty-five but no more than one hundred dollars.
Keywords: CARRY - CONCEALED